If it's not what You are looking for type in the equation solver your own equation and let us solve it.
19=5x-4(x-6)
We simplify the equation to the form, which is simple to understand
19=5x-4(x-6)
Reorder the terms in parentheses
19=5x+(-4x+24)
Remove unnecessary parentheses
+19=+5x-4x+24
We move all terms containing x to the left and all other terms to the right.
-5x+4x=+24-19
We simplify left and right side of the equation.
-1x=+5
We divide both sides of the equation by -1 to get x.
x=-5
| -3-6a=9 | | x^2-2x-17=-3 | | x^2+4x-4=-12 | | a^2-10a+26=5 | | -20=3x-2(x+6) | | v^2+2v-28=-4 | | 8=5x-27 | | 2a-7=-11 | | 125-1234567890123456789012345678901234567890123456789012345678901234567890.000000000000000000000000000100+2x=0.01 | | -4x-2(8x+1)=2(10x+7) | | 340=-16t^2-4t+472 | | x^2+6x-18=-2 | | 6x-4(2x+7)=-42 | | lnx=2+ln(x-4) | | 1 = b2– 1 | | v^2-6v-12=5 | | 9=4+-y | | a-60=2a | | 1947x+18452=2 | | 3=-6x+3(3x-8) | | 3-8a=35 | | x^2-2x-1=4 | | -17-6x=9x+22 | | 100x-10=2 | | 15y=120 | | 0.50x=0.20x+7.50 | | -2x+6(-3x-8)=52 | | 8x^2+22x+21=0 | | -6f+16=2f-11 | | y-17=-75 | | -6x+6(3x+3)=-54 | | -10x-27+12x=31 |